2018
DOI: 10.1002/ajcp.12272
|View full text |Cite
|
Sign up to set email alerts
|

Natural Environments Near Schools: Potential Benefits for Socio‐Emotional and Behavioral Development in Early Childhood

Abstract: Features of the natural environment such as tree canopy and green space have been found to promote health and well-being; however, minimal research has investigated potential benefits of nature near schools for early childhood development. This study examined differences in teacher ratings of preschoolers' socio-emotional and behavioral functioning in relation to the presence of natural elements (e.g., trees, parks) near children's homes and schools. Students' development of emotional and behavioral regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 42 publications
2
45
1
1
Order By: Relevance
“…Availability (i.e., quantity) of nature or public open space in the neighborhood was measured in various ways including: Proportion of nature/public open space in a buffer area; satellite imagery around home; and parent-reported availability. Three studies used the proportion of natural space or public open space within a pre-defined area around a child’s residence [54,55,56]. In Australia, higher proportion of public open space in the child’s area of residence was associated with lower mental health difficulties [55].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Availability (i.e., quantity) of nature or public open space in the neighborhood was measured in various ways including: Proportion of nature/public open space in a buffer area; satellite imagery around home; and parent-reported availability. Three studies used the proportion of natural space or public open space within a pre-defined area around a child’s residence [54,55,56]. In Australia, higher proportion of public open space in the child’s area of residence was associated with lower mental health difficulties [55].…”
Section: Resultsmentioning
confidence: 99%
“…Further, when stratifying by maternal education (low vs. high) and by gender, this study found significant differences between subgroups; for example, higher proportion of natural space was associated with fewer peer problems in young children with less-educated mothers, and more prosocial behavior in children with more-educated mothers [54]. In the United States, a higher proportion of tree canopy around children’s residence was associated with improved self-regulation and decreased behavior concerns, but not with peer or teacher relationships or children’s initiative to meet their own needs [56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords such as ‘natural environment’, ‘natural playground’, ‘green schoolyard’ etc., were up to now used to a rather limited extent within the field. However, these keywords might gain traction in the coming years as can be suspected from publications that appeared after the final search for this review had been conducted [39,40]. For reasons of comparability, use of the same outcome measures as in earlier research, such as the SDQ, is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that LID and GI improve the educational performance, and socioemotional, behavioral, and cognitive development of students [91,92]. In particular, preschoolers at educational risk were found to have greater development of independence and social skills when enrolled to schools with higher levels of plant-based LID [91]. The fourth criteria (SEI 4 ) assigns priority to sites that are closer to hospitals to improve the health status of patients.…”
Section: Socioeconomic Index (Sei) Developmentmentioning
confidence: 99%